1996
DOI: 10.1055/s-2007-972865
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moderate Aerobic Training on Lymphocyte Proliferation

Abstract: The purpose of this study was to determine the effect of 12 wks of aerobic training on resting lymphocyte number and proliferation, and immunoglobulin and cytokine levels. Eleven college-aged males (training group = EX) performed 30 min of cycling at 75% of VO2peak, 3 days/wk with VO2peak assessment and blood samples taken at 0,8 and 12 wks. A group of 10 sedentary controls (CT) underwent the same testing protocol. Lymphocyte proliferation response to phytohemagglutinin (PHA) and pokeweed mitogen (PWM) was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 1 publication
1
28
0
1
Order By: Relevance
“…The mechanisms involved in the diVerent eVects of exercise on the immune system are not fully understood and seem to be multi-factorial, including endocrine changes and alterations in plasma glutamine concentrations (Mitchell et al 1996;Nieman and Pedersen 1999;Pedersen and Toft 2000;Bassit et al 2000;Castell 2002Castell , 2003Cunha et al 2003;Costa Rosa 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in the diVerent eVects of exercise on the immune system are not fully understood and seem to be multi-factorial, including endocrine changes and alterations in plasma glutamine concentrations (Mitchell et al 1996;Nieman and Pedersen 1999;Pedersen and Toft 2000;Bassit et al 2000;Castell 2002Castell , 2003Cunha et al 2003;Costa Rosa 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mackinnon (1996) reports that the IgA class of antibodies primarily interact and defend the various secretory surfaces from invasion; therefore, [IgA] can readily be measured in tears, saliva, or fluids from the respiratory, genito-urinary and gastro-intestinal tracts. Although heavy exercise has been shown to decrease markedly the IgA concentrations of both nasal and salivary ([IgA s ]) samples (Tharp and Barnes 1989;Mackinnon and Jenkins 1993), the few studies that have examined the effects of moderate exercise on [IgA s ] have been inconclusive (Schouten et al 1988;Nehlsen-Cannarella et al 1990;Karper and Goldfarb 1995;Mitchell et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that strenuous swimming training of athletes increases susceptibility to infection and that moderate intensity exercise reduces immunity in young healthy individuals (Mitchell et al, 1996;Pedersen, 1997;Pedersen et al, 1998). Peijie et al (2003) reported that 6-week heavy load training induced immune system dysfunction in SD rats, but moderate exercise increased T-cell subsets relative to heavy load training.…”
Section: Discussionmentioning
confidence: 99%